Integrerade navigationssystem - En studie om användarvänlighet, komplexitet och utbildning - Britz, Egon; Holmberg, Patrik (My University, 2017)
Integrated navigation systems are complex. Today, it takes a lot of knowledge to be able to handle these advanced functions that can be found within the ECDIS, conning and radar systems. It is of great use to be able to know what will happen to the specific systems when a system or sensor in the chain around it fails or delivers bad data. The study will be based on the following questions: What is the view by Swedish officers around the user-friendliness of radar, ECDIS and conning systems? What are Swedish officers’ views on the importance of having drills related to integrated navigation systems? How do Swedish officer’s see their own knowledge and understanding around the topic integrated navigation systems to be able to monitor and operate these systems with familiarity? The study is supported by a survey where the participants were able to express their experience regarding integrated navigation systems. Also, the researchers were able to examine how the officers see their own understanding in regards to integrated navigation systems. After that three semi-structured interviews were conducted. First, with a manufacturer of integrated navigation systems and then followed by two senior Swedish officers. The interviews were a follow-up on the survey results but also it provided an opportunity to more qualitative data on user-friendliness, drills and the general knowledge by officers. The result shows that education regarding integrated navigation systems has been deficient. System failures do occur frequently but no clear structure on how to handle the situations that follow has been made. Officers point out that the systems are complex, the user-friendliness varies and that drills and education should be introduced. The solution is believed to be a regulation that regulates education should be given during school and during familiarization on board. It should also state that drills regarding integrated navigation systems should be conducted on a regular basis on board.
Keywords: Transport; Transportteknik och logistik; Annan teknik; Transport; Transport Systems and Logistics; Other Engineering and Technologies